Efektivitas Edukasi Health Belief Model dalam Perubahan Pengetahuan dan Perilaku Pasien Tuberkulosis - Fitriyani, Lia; Dwijayanti, Fifi; Ruswandi, Umar; Afriansyah, Eddy; Purwadi, Hendro (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Indonesia ranks second in the incidence of tuberculosis after India with 1.06 million cases and 134,000 deaths. About 15 people die from TB every hour. The number of tuberculosis cases in Depok City in 2019 was 4,695 cases, in 2020 there were 3,311 cases, in 2021 there were 3,974 cases and in 2022 there were 6,549 cases.The aim of this research is to determine the effectiveness of health belief model (HBM) education in changing tuberculosis knowledge and behavior. This research uses a quasi-experimental design. The quasi-experimental approach used was a one group pretest–posttest design. This research was conducted in Depok City for 2 months in January-February 2024. The sample in this study was 60 patients. Data collection uses a questionnaire. Data analysis was carried out using the Wilcoxom test. The results of this research are that the application of the Health Belief Model is effective in increasing knowledge (p value = 0.000) and behavior (p value = 0.000) of tuberculosis patients in Depok City. The conclusion of this research is that providing education using the health belief model influences knowledge and behavior. The suggestion in this research is to carry out regular evaluations to measure the effectiveness of the intervention and make adjustments if necessary.